Robbery of Financial Institutions in Indiana, 1982-1984 - Baumer, Terry L. ([Verlag nicht ermittelbar], 1990)
The goals of this data collection were to provide information on robbery-related security measures employed by financial institutions, to identify factors that contribute to robbery, and to study the correlates of case disposition and sentence length of convicted robbers. The collection compares banking institutions that have been robbed with those bank offices that have not been robbed to provide information on factors that contribute to these robberies. The office-based file includes variables designed to measure general office characteristics, staff preparation and training, security measures, characteristics of the area in which the banking institution is located, and the robbery history of each institution. The incident-based file includes variables such as the robber's method of operation and behavior, the employee's reaction, the characteristics of the office at the time of the robbery, and the apprehension of the offender. Also included is information on the status of the investigation, reasons involved in solving the robbery, status of prosecution, ultimate prosecution, and sentence in length.